(untitled) (World Bulletin of Social Sciences, 2023)
In this article, the history of the study of Zingiber officinale L., the worldwide scientific research on the species, ZINGIBER OFFICINALE. Botanical description of L., medicinal properties of Zingiber officinale L. are discussed. Ginger (Zingiber officinale L) is a spice and medicinal plant belonging to the ginger family. Ginger has been used in folk medicine in India and China since ancient times